PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS TERHADAP ALOKASI BELANJA MODAL DENGAN PERTUMBUHAN EKONOMI SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Pemerintah Kabupaten/Kota Di Provinsi Riau) - Rilian Pratama; Yesi Mutia Basri; Supriono Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
to capital expenditure. These factors are Local Revenues, General Allocation Fund, Special Allocation Fund To Capital Expenditure With Economic Growth As A Moderating Variable. The population that will be used in this research are districit/municipal governments in the Province Of Riau. The Method used was Purposive Sampling due to availability of data. Collecting data was conducted from governments financial statements from Central Bureau of Statistics. The method of data analysis in this study is use multiple liniear regression with SPPS version 21. The results of this study prove that local revenues, general allocation fund and special allocation fund significantly positive affect to capital expenditure. While economic growth is not moderate the relationship between local revenues and special allocation fund to capital expenditure at district/municipal in the Province of Riau. The Amount of R Square (R2) is 0.597 gives the sense that the rate is 59.7% of level capital expenditure can be explained by Local Revenues, General Allocation Fund, Special Allocation Fund, Economic Growth task while 40.3% can be explained by other variabels that are not tested in this study. Keyword : Local Revenues, General Allocation Fund, Special Allocation Fund, Economic Growth